Ethics and the conduct of business - Boatright, John Raymond (Pearson Prentice Hall, 2007)
Focusing on ethical issues facing corporate managers making decisions that impact employees, customers, or the general public, this textbook presents a moral theory that rests on concepts from Bentham's utilitarianism, Kant's moral imperative, and other philosophical perspectives and applies it to ethical problems that arise in the business world. These issues include whistle-blowing; trade secrets and conflict of interest; privacy; discrimination and affirmative action; women and family issues; unjust dismissal; marketing, advertising, and product safety; occupational health and safety; finance; corporate responsibility and governance; and international business. (booknews.com)